Effectiveness Analysis of Safe Work System Implementation Using the Swiss Cheese Model Approach - Suparli Suparli; Emmy Pratiwi (Journal of Social Research, 2026)
Workplace accidents in the mining industry remain a critical global concern due to their impact on worker safety and operational efficiency. A major coal mining company in Indonesia, experienced an increasing number of accidents from 2022 to 2024, despite implementing a five-layer Safe Work System (SBS). This study aims to analyze the causes of these accidents using the Swiss Cheese Model to identify systemic weaknesses across organizational, planning, operational, technological, and contact defense layers. A qualitative case study approach was employed, complemented by descriptive statistical analysis of 2,413 findings from 435 accident reports. Each incident was mapped to the five SBS layers to determine frequency, contribution, and interactions among failures. The results indicate that Layer III (Work Readiness & Monitoring) was the dominant contributor (45.67%), followed by Layers II (Plan Readiness) and I (Organization Roles & Responsibility), highlighting operational deviations influenced by latent managerial and planning weaknesses. Layers IV (Preventive Defense) and V (Contact Defense) played supporting roles, emphasizing the importance of technology and emergency preparedness. The study concludes that accidents are systemic, resulting from alignment failures across multiple defense layers. Strengthening organizational policies, risk-based planning, operational monitoring, and technology integration is essential to improve safety maturity. Future research should explore the application of predictive safety analytics and multi-site comparisons to enhance proactive accident prevention in mining operations.